Application of Asbab Al-Nuzul in Understanding Contextual Meaning of Everyday Life - Erma Fitriya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This article aims to outline the use of asbab al-nuzul in understanding the contextual meaning of Qur'anic verses and their relevance in everyday life. The method applied is conceptual analysis based on literature review, by tracing the relationship between the historical context of the verse's revelation (asbab al-nuzul) and contemporary interpretation of the Qur'ān's universal message. The study found that asbab al-nuzul has a strategic role in helping Muslims understand both the specific and universal meanings of Qur'anic verses. The main findings show that the application of asbab al-nuzul can be a practical guide in various areas of life, such as social justice, education, and religious tolerance. In addition, this study confirms that the flexibility of Islamic law allows for adjustments to the modern context without compromising the essence of its teachings. This article recommends the development of asbab al-nuzul studies to support a more relevant understanding of Qur'anic values in the contemporary era.